Simple and Low-Cost Chemical Experiment Kits to Observe the Concept of Gas Laws - Zidny, Robby; Fadhilah, Geby Ayu; Melda, Githa Eryani; Sholihah, Izmi Izzatus; Widiastuti, Nabila Lailil; Haerunnisa, Nina; El Islami, R. Ahmad Zaky (Jurnal Penelitian dan Pembelajaran IPA, 2019)
This study aimed to develop a simple and low-cost chemical experiment kits to facilitate students in the school which has limited chemistry laboratory facilities. The topic of the experiment was the concepts of gas laws. The research was conducted in a private school in a rural area of Banten, Indonesia using educational research and development method. 10th-grade high school students (n=27) participated in this study. The research result indicated that the experiment kits facilitate the teacher to explain the chemical concepts of gas laws. Learning using the gas laws experiment kits also had positive responses from students. The results showed that the kits were eligible to be applied in the high school chemistry learning.